Investigation of the use of recombinant BCG, expressing the major capsid protein (LI) of human papillomavirus type 16, as a candidate vaccine for cervical cancer - MacLean, James Malcolm (Division of Virology, 2014)
Includes bibliographical references (leaves 214-236).